Analisis Pengaruh Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien Peserta Jaminan Kesehatan Nasional di Indonesia - Aliyyah, Annisa Fijjannah; Difhanny, Chairunnisyah Nurma; Ananda, Dhea Namira; Rahma, Desfi; Jayanti, Priska Dwi; Agustina, Dewi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Satisfaction of health service providers is very important, but satisfaction is often neglected or forgotten. Patient satisfaction is an important aspect in measuring the quality of health services. Research objective: analysis of the effect of health service quality on patient satisfaction of JKN participants in Indonesia. The state of public health greatly affects health services in Indonesia. The type of research carried out is The method used in writing literature review. The population is JKN participants in Indonesia. Based on the results of a literature review of 10 journals obtained, it shows that there is a significant relationship between the effect of the quality of health services on the satisfaction of patients participating in the national health insurance in Indonesia. In this literature review, it is also concluded that there is a relationship between the quality of health services and the satisfaction of patients participating in the National Health Insurance (Ï<0.05).